2016
DOI: 10.1126/scitranslmed.aab4109
|View full text |Cite
|
Sign up to set email alerts
|

Mavoglurant in fragile X syndrome: Results of two randomized, double-blind, placebo-controlled trials

Abstract: Fragile X syndrome (FXS), the most common cause of inherited intellectual disability and autistic spectrum disorder, is typically caused by transcriptional silencing of the X-linked FMR1 gene. Work in animal models has described altered synaptic plasticity, a result of the up-regulation of metabotropic glutamate receptor 5 (mGluR5)-mediated signaling, as a putative downstream effect. Post hoc analysis of a randomized, placebo-controlled, crossover phase 2 trial suggested that the selective mGluR5 antagonist ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
187
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(191 citation statements)
references
References 33 publications
3
187
1
Order By: Relevance
“…While preliminary molecular characterization of epigenetic (full-methylation) patterns of ASD in FXS in the Phase II trials [82] has suggested that methylation status may constitute a treatment-sensitive biomarker for predicting response to a mGluR5 inhibitor [83,84], this finding was not replicated in two large phase III trials of mavoglurant [85]. Neither of these studies, as reported by Berry-Kravis and colleagues [85], reached the primary efficacy end point of improvement on behavioral symptoms measured by the Aberrant Behavior Checklist-Community edition using the FXS-specific algorithm (ABC-CFX) after 12 weeks of treatment with mavoglurant. These studies with mavoglurant also indicated that the methylation state of the FMR1 promoter was also not able to predict drug efficacy.…”
Section: Targeted Treatments In Fragile X Syndromementioning
confidence: 71%
See 2 more Smart Citations
“…While preliminary molecular characterization of epigenetic (full-methylation) patterns of ASD in FXS in the Phase II trials [82] has suggested that methylation status may constitute a treatment-sensitive biomarker for predicting response to a mGluR5 inhibitor [83,84], this finding was not replicated in two large phase III trials of mavoglurant [85]. Neither of these studies, as reported by Berry-Kravis and colleagues [85], reached the primary efficacy end point of improvement on behavioral symptoms measured by the Aberrant Behavior Checklist-Community edition using the FXS-specific algorithm (ABC-CFX) after 12 weeks of treatment with mavoglurant. These studies with mavoglurant also indicated that the methylation state of the FMR1 promoter was also not able to predict drug efficacy.…”
Section: Targeted Treatments In Fragile X Syndromementioning
confidence: 71%
“…For example, phase IIb/III clinical trials studying social and other behaviors in individuals with ASD in FXS using a subtype-selective mGluR5 inhibitors (basimglurant and mavoglurant) have shown no therapeutic benefits in FXS patients for unknown reasons [81]. While preliminary molecular characterization of epigenetic (full-methylation) patterns of ASD in FXS in the Phase II trials [82] has suggested that methylation status may constitute a treatment-sensitive biomarker for predicting response to a mGluR5 inhibitor [83,84], this finding was not replicated in two large phase III trials of mavoglurant [85]. Neither of these studies, as reported by Berry-Kravis and colleagues [85], reached the primary efficacy end point of improvement on behavioral symptoms measured by the Aberrant Behavior Checklist-Community edition using the FXS-specific algorithm (ABC-CFX) after 12 weeks of treatment with mavoglurant.…”
Section: Targeted Treatments In Fragile X Syndromementioning
confidence: 79%
See 1 more Smart Citation
“…However, a small subgroup of participants with fully methylated FMR1 promoter regions showed significant improvements in stereotypic behavior, hyperactivity, and inappropriate speech as measured by the Aberrant Behavior Checklist-Community Edition (ABC-C) as well as in the overall ABC-C total score. These results encouraged two larger, multinational double-blind, placebo-controlled and parallel group trials of mavoglurant: one in adolescents (Phase III trial) and one in adults (Phase II trial) (23). In each study, participants were stratified into partial or full FMR1 methylation groups and then randomized to placebo or one of three doses of mavoglurant: 25 mg BID, 50 mg BID, or 100 mg BID.…”
Section: Metabotropic Glutamate Receptor 5 (Mglur) Antagonistsmentioning
confidence: 99%
“…We often are quick to conclude that "negative" findings in a trial prove that a treatment is ineffective under all conditions or that the presumed underlying pathophysiological mechanisms are not valid. However, as reinforced by the well-designed, properly powered study in this issue by Berry-Kravis et al (1), negative findings can provide an opportunity opportunity to reflect on clinical trial design and implementation, as well as the underlying mechanistic motivations, and provide lessons for treatment studies of neurodevelopmental disorders in general. Berry-Kravis et al highlight key themes to consider in clinical trials: choice of treatment group, target engagement, selection of outcome measures, and the impact of the placebo effect.…”
mentioning
confidence: 99%